Correlation between the elevated level of interleukin-6 following actemra administration and the mortality rate of seven severe COVID-19 patients - Ardabili, Ayda Vakili; Sarabi, Shahnaz Fooladi (International Journal Of Community Medicine And Public Health, 2024)
The escalation and involvement of Interleukin 6 (IL-6) in the pathogenesis of COVID-19 have been documented in numerous studies and are recognized as a diagnostic criterion, disease biomarker, and therapeutic objective. Our study aims to explore the correlation between the elevated level of IL-6 following actemra administration and the mortality rate of seven severe COVID-19 patients who were admitted to the special care department of Ardabil city hospital. In this case-series study, 7 patients with severe COVID-19 were admitted to the special care department of Ardabil city hospital were included in the study. Venous blood samples (3 cc) were taken in admission and after actemra injection. The demographic characteristics of the patients, including age, sex, duration of hospitalization, need for intubation, BMI, and interleukin 6 levels, were recorded in a checklist. The patients were then monitored for their clinical course, disease outcome, and complications. The mean IL-6 before and after actemra was 413.57±138.38 and 805.50±128.18, respectively and the difference was significant. After treatment by actemra, 71.4% of patients were discharged from hospital without mortality. Although elevated IL-6 levels have been associated with cytokine storms and unfavorable consequences in COVID-19 patients. This report indicates that high interleukin levels do not guarantee mortality. Young individuals without underlying conditions were ultimately discharged from the ICU despite severe inflammation, thanks to timely treatment and albeit with severe disability.